2016
DOI: 10.1371/journal.pone.0147544
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Hospital Acquired Infections and Antimicrobial Use in Vietnamese Adult Intensive Care Units

Abstract: BackgroundVietnam is a lower middle-income country with no national surveillance system for hospital-acquired infections (HAIs). We assessed the prevalence of hospital-acquired infections and antimicrobial use in adult intensive care units (ICUs) across Vietnam.MethodsMonthly repeated point prevalence surveys were systematically conducted to assess HAI prevalence and antimicrobial use in 15 adult ICUs across Vietnam. Adults admitted to participating ICUs before 08:00 a.m. on the survey day were included.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 20 publications
6
113
1
6
Order By: Relevance
“…The prevalence of CRE, including CP-CRE, is high in the tertiary hospitals of the larger South Asian countries (10, 53, 62-71, 75, 82, 83, 99, 101, 102) but much lower in similar hospitals in Southeast Asia (74,114,120,121,129,134,142,147,149,150,157,161). As seen by the numerous reports of CP-CRE exportation from South and Southeast Asia (6,174,(176)(177)(178)(179)(180)(181)(182)(183)(184), international dissemination of CP-CRE appears to be a far greater problem than that of CRAB, and it will conceivably be more difficult for other countries to control CP-CRE within their own borders if this is also not tackled at its root in South and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of CRE, including CP-CRE, is high in the tertiary hospitals of the larger South Asian countries (10, 53, 62-71, 75, 82, 83, 99, 101, 102) but much lower in similar hospitals in Southeast Asia (74,114,120,121,129,134,142,147,149,150,157,161). As seen by the numerous reports of CP-CRE exportation from South and Southeast Asia (6,174,(176)(177)(178)(179)(180)(181)(182)(183)(184), international dissemination of CP-CRE appears to be a far greater problem than that of CRAB, and it will conceivably be more difficult for other countries to control CP-CRE within their own borders if this is also not tackled at its root in South and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The results from recent reports (published from 2010) are summarized in Table 5. The prevalence of CRAB in Vietnamese hospitals is very high, ranging from 43% in a pediatric hospital in Ho Chi Minh City to 92% in a tertiary referral hospital in Hanoi (142)(143)(144)(145)(146)(147). Unfortunately, the bulk of the studies were based on ICUs, where carbapenem resistance rates are usually higher (142)(143)(144)147).…”
Section: Vietnam There Is No National or Regional Antimicrobial Resimentioning
confidence: 99%
“…This in combination with a high rate of antimicrobial use illustrates the urgent need to improve rational antimicrobial use and infection control efforts [41][42][43]. However, from a study, it was partially confirmed that ICU patients would be exposed to water amoeba-associated microorganisms and provides information about the magnitude of AAM infection in ICU patients, especially patients that have a prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, Acinetobacter species and P. aeruginosa are emerging as pathogens that frequently cause infections in patients with high sever consequences in intensive care units (22 including mechanisms and risk factors of development of resistance as well as the effectiveness and toxicity of various therapeutic options. In multivariate analysis, the strongest risk factors for hospital-acquired infections acquired in ICU were intubation, urinary catheter, severity of illness, involvement of a family member in patient care, and surgery after admission (23).…”
Section: Discussionmentioning
confidence: 99%